P087 ILEAL BIOMARKER OF INNATE IMMUNE ACTIVATION CAN PREDICT CLINICAL RESPONSE TO VEDOLIZUMAB IN CROHN'S DISEASE. (7th February 2019) - Osterman, Mark T; Gordon, Ilyssa O; Davis, Elisabeth M; Ciorba, Matthew A; Glover, Sarah C; Abraham, Bincy P; Khan, Freeha; Shen, Bo; Yee, Eric; Allard, Felicia; Liu, Julia J
Abstract: Introduction: Mucosal barrier dysfunction to luminal microbes plays a crucial role in the development of intestinal inflammation in Crohn's disease (CD). Recently, an inflammatory form of intestinal epithelial cell (IEC) death resulting from innate immune activation, termed pyroptosis, was proposed as a possible cause of this barrier defect. We hypothesize that ileal IEC pyroptosis, as a marker of mucosal barrier dysfunction, may be used to predict clinical response of biologic therapy in CD patients. Vedolizumab is an anti-integrin monoclonal antibody approved for the treatment of CD. The aim of this multi-centered study was to determine the predictive value of pre-treatment ileal IEC pyrotposis for clinical response to vedolizumab in CD. Methods: CD patients aged 18 to 78 years from five American IBD centers who had ileal biopsies obtained during colonoscopy before vedolizumab were enrolled. Clinical response, defined as a reduction of Harvey-Bradshaw Index (HBI) of ≥5 points from the pre-treatment baseline, and clinical remission, defined as HBI <5, was determined at ≥6 months after therapy by chart review. Biopsy samples were sectioned and stained for IEC pyroptosis using the Maximus Barrier Assay kit (Maximus Diagnostics LLC). Samples with a minimum of 10 intact villi per patient were analyzed by blinded pathologists for quantitation of ileal IEC pyroptosis. The primary study outcome was clinical response rate to vedolizumab stratified by pre-treatment ileal pyroptosis, using 18 positive cells/1000 IECs as a cut-point. Results: A total of 80 CD patients were enrolled and 5 were excluded from further analysis due to inadequate biopsy samples for IEC pyroptosis quantification. In the remaining 75 patients (40 M, 35 F), the median age was 47 (19, 78) years; 44 (59%) had clinical response to vedolizumab, and 25 (33%) were in clinical remission. There were no significant differences in baseline patient or disease characteristics between responders and non-responders. The clinical response rate in patients with IEC pyroptosis below the critical cut-point of 18 positive cells / 1000 IECs was significantly higher compared to those above: 74% (29/39) vs. 44% (16/36), odds ratio 3.7 (1.4, 10.0), p=0.008. IEC pyroptosis in responders and non-responders were 16.8 ± 11.8 vs. 24.5 ± 11.6 positive cells / 1000 IECs, respectively (p=0.007). The probability of response to vedolizumab was inversely related to the level of ileal IEC pyroptosis, with IEC pyroptosis of > 39 positive cells / 1000 IECs associated with a clinical response rate of 17% (1/6), while a level of <13 positive cells / 1000 IECs was associated with a 90% (18/20) clinical response. Conclusion: Ileal biopsy IEC pyroptosis can predict clinical response to vedolizmab therapy in Crohn's disease patients. Clinical response stratified by pre-treatment ileal pyroptosis